Polarization of Issues Related to Permanent Voter Data (DPT) and Its Impact on Governance - Khuriyatul Husna; Ridho Ramadhan Arfi; Alexsander Yandra; Dian Rianita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Recurring issues surrounding the permanent voter list (DPT) in general and local elections in Indonesia reflect systemic weaknesses in election governance. This study aims to map the polarization of issues related to the DPT and analyze their impact on public administration. A qualitative literature review was conducted on 47 selected journal articles obtained through Google Scholar as the main entry point due to its accessibility and broad coverage. Various types of sources, including journal articles, theses, reports, and preprints, were used, enabling researchers to capture a more diverse literature landscape, especially in local or regional contexts where publications are not always indexed in paid databases; the ease of initial filtering also meant faster results when searching for specific keywords, allowing researchers to compile an initial list of relevant articles for further screening; and the diversity of languages and sources enabled the discovery of Indonesian or regional works that are often underrepresented in international paid databases, making them relevant for local studies on DPT and governance. The findings show that Voter List issues can be categorized into three types of polarization: structural versus cultural, technological versus manual, and centralization versus decentralization. These issues lead to reduced electoral legitimacy, budget inefficiency, and declining public trust. In conclusion, voter list issues are not merely administrative problems but also serious threats to the quality of democracy and effective governance. Comprehensive reforms involving strengthened regulations, institutional capacity building, and technological optimization are urgently needed to enhance the integrity of voter data in future elections.